Kinetics of rabies antibodies as a strategy for canine active immunization - Babboni, Selene Daniela [UNESP] (2014)
Background: Rabies, a zoonosis found throughout the globe, is caused by a virus of the Lyssavirus genus. The disease is transmitted to humans through the inoculation of the virus present in the saliva of infected mammals. Since its prognosis is usually fatal for humans, nationwide public campaigns to vaccinate dogs and cats against rabies aim to break the epidemiological link between the virus and its reservoirs in Brazil.Findings: During 12 months we evaluated the active immunity of dogs first vaccinated (booster shot at 30 days after first vaccination) against rabies using the Fuenzalida-Palacios modified vaccine in the urban area of Botucatu city, Sao Pauto state, Brazil. Of the analyzed dogs, 54.7% maintained protective titers (>= 0.5 IU/mL) for 360 days after the first vaccination whereas 51.5% during all the study period.Conclusions: The present results suggest a new vaccination schedule for dogs that have never been vaccinated. In addition to the first dose of vaccine, two others are recommended: the second at 30 days after the first and the third dose at 180 days after the first for the maintenance of protective titers during 12 months.